1995
DOI: 10.1111/j.1651-2227.1995.tb13654.x
|View full text |Cite
|
Sign up to set email alerts
|

Arterial oxygen saturation in infants at risk of sudden death: influence of sleeping position

Abstract: To study the possible influence of sleeping position on arterial oxygen saturation, measured by pulse oximetry (SpO2), 7-h overnight recordings of breathing movements and ECG were performed in 43 infants (median age 2.4 months, range 0.2-11 months) at increased risk of sudden infant death syndrome (SIDS). Infants were randomly allocated to start sleeping either in their usual sleeping position or in the opposite position. After 3.5 h, all infants were gently turned over. Thus, each infant served as their own c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
1

Year Published

1997
1997
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 15 publications
1
13
1
Order By: Relevance
“…Besides, causal factors include rebreathing of expired air when laying facedown [6,40], possibly in combination with cushions used before death [39], as can be seen from our data. It has been reported, however, that arterial oxygen saturation in the prone and supine position were similar [57]. Moreover, complete covering of the head is a predominant risk factor for cot death in our study, where 95.5% of all babies who were entirely covered by their blanket have been found facedown.…”
Section: Discussioncontrasting
confidence: 58%
“…Besides, causal factors include rebreathing of expired air when laying facedown [6,40], possibly in combination with cushions used before death [39], as can be seen from our data. It has been reported, however, that arterial oxygen saturation in the prone and supine position were similar [57]. Moreover, complete covering of the head is a predominant risk factor for cot death in our study, where 95.5% of all babies who were entirely covered by their blanket have been found facedown.…”
Section: Discussioncontrasting
confidence: 58%
“…30,31 The second search: 'infant AND prone AND pulse oximet* AND SIDS' resulted in three papers. 30,32,33 Removing infant from the search for 'prone AND pulse oximet* AND SIDS' yielded the same three results. 30,32,33 Expanding the search to the general PubMed database (not limited to the Clinical Queries section) with the limit of infant (age birth -23 months) and the search strategy: 'pulse oximetry AND prone AND SIDS' yielded five papers.…”
Section: Methodssupporting
confidence: 62%
“…The Sahni et al 30 study examined low birth weight (LBW) and the Saiki et al 34 and Poets et al 32 studies examined premature babies, both of which are populations at increased risk of SIDS 8 and therefore not relevant to our population of interest. The Poets et al study from 1995 33 also included babies at increased risk of SIDS, either because they were premature, had a sibling who died of SIDS, or had a suspected airway obstruction. Furthermore, Poets et al found no significant differences in oxygen desaturations measured 32 while Saiki et al 34 found no significant differences in oxygen saturation levels between prone or supine position lying infants.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies in preterm infants of Ͼ36 weeks of postconceptional age who are no longer experiencing respiratory distress, as well as in term infants, have not demonstrated improved oxygenation in the prone position. [22][23][24] Thus, there should be no particular advantage to prone sleeping for preterm infants who have resolved their respiratory distress at the time of discharge. In addition, the observations that prone sleeping is associated with deeper levels of sleep may put the somewhat weaker and less mobile preterm at greater risk of being trapped in a position from which it cannot extract itself.…”
Section: Discussionmentioning
confidence: 99%